A dual-ion accepting vanadium carbide nanowire cathode integrated with carbon cloths for high cycling stability. Issue 40 (12th October 2020) - Nam, Sanghee; Thangasamy, Pitchai; Oh, Saewoong; Mahato, Manmatha; Koratkar, Nikhil; Oh, Il-Kwon
Abstract : Herein, we report vanadium carbide (V8 C7 ) nanowires (NWs) axially grown on carbon cloths (CCs) as a dual-ion accepting cathode for both lithium (LIBs) and sodium-ion batteries (SIBs). Abstract : Herein, we report vanadium carbide (V8 C7 ) nanowires (NWs) axially grown on carbon cloths (CCs) as a dual-ion accepting cathode for both lithium (LIBs) and sodium-ion batteries (SIBs). Using a facile hydrothermal method, we grew V2 O3 NWs on CCs and subsequently reduced them to V8 C7 by annealing with carbon sources under a H2 /Ar atmosphere. In striking contrast to V2 O5 NW cathodes obtained by annealing under air, the V8 C7 NWs exhibit outstanding cycling stability during 500 cycles, and good rate capability for both LIBs and SIBs. V8 C7 NWs as cathode active materials for LIBs exhibited 203.9 mA h g −1 specific capacity at 0.1 C after 500 cycles, 91.12% cycling retention and a coulombic efficiency of 99.84%. As cathodes in SIBs, the V8 C7 NWs delivered 176.34 mA h g −1 specific capacity at 0.1 C during 300 cycles. Their defect sites by removal of the oxygen framework in V2 O3 NWs have a high surface area (183.27 m 2 g −1 ) and the unique 1D NW structure highly mitigates the volume changes during charge and discharge showing a superior electrochemical performance. Compared to commercially available cathodes, V8 C7 nanowires have very good cycling stability and enhanced electrical conductivity. Moreover, the synergistic effect with 3D CCs utilized here as a current collector provides a large number of cation-accessible active sites in conjunction with high electrical conductivity and chemical stability.